"Unsympathetic Users" : An Ethnoarchaeological Examination of Inuit Responses to the Changing Nature of the Built Environment - Dawson, Peter C. (ARCTIC, 1995)
Recent trends in modern architectural theory stress the dynamic relationship that exists between culture and the built environment. Such theories hold that because different cultures are characterized by distinctive types of economic, social, and ideological relationships, they require different forms of spatial order to sustain them. Through the adoption of such a perspective, this paper examines the effects of Euro-Canadian prefabricated housing on modern Inuit groups in the central and eastern Canadian Arctic. Preliminary results suggest that the "alien" spatial environments of the southern-style prefabricated house may have contributed to increasing gender asymmetry, a transformation of social relations through the delayed resolution of interpersonal conflicts, confusion over how, when and where to conduct various household activities, and a loss of cultural identity among contemporary Inuit.Key words: human spatial behaviour, government housing, Inuit, gender, acculturation, northern communities Les tendances récentes dans la théorie de l'architecture moderne insistent sur le rapport dynamique existant entre la culture et le cadre bâti. De telles théories soutiennent que, vu que différentes cultures se caractérisent par des types distincts de rapports économiques, sociaux et idéologiques, elles ont besoin pour se maintenir de différentes formes d'aménagement des volumes et des espaces. En adoptant une telle perspective, cet article examine les effets des habitations eurocanadiennes préfabriquées, sur les groupes inuits modernes du centre et de l'est de l'Arctique canadien. Les résultats préliminaires suggèrent que les aménagements «étrangers» des volumes et des espaces des maisons préfabriquées conçues dans le sud pourraient avoir contribué à une augmentation de l'asymétrie entre les sexes, à une transformation des rapports sociaux par la résolution tardive des conflits interpersonnels, à une certaine confusion concernant l'exécution ses diverses activités au foyer (comment, quand et où), et à une perte ...